2019
DOI: 10.23925/2179-3565.2019v10i3p48-58
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Strategic Orientations on Organizational Performance of Smes: Empirical Evidence From Pakistan

Abstract: Strategic orientations like Market orientation (MO) and Learning orientation (LO) play critical role in improving the performance of both large and small scale businesses. This paper investigate the relationship between LO and organizational performance with MO as moderator. The current study reports the findings of two hundred and seven owners or managers of Small and Medium Sized Enterprises (SMEs) in Pakistan. The findings of the study indicate a positive relationship between LO and organizational performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Meanwhile, Hussain (2019) in another study concluded that market orientation has a significant influence on marketing performance. Manzano et al (2006) and Susanto (2012) also state that if market orientation increases, marketing performance will also increase.…”
Section: International Journal Of Social Science Research and Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, Hussain (2019) in another study concluded that market orientation has a significant influence on marketing performance. Manzano et al (2006) and Susanto (2012) also state that if market orientation increases, marketing performance will also increase.…”
Section: International Journal Of Social Science Research and Reviewmentioning
confidence: 99%
“…On the other hand, Ferdinand (2002), Baker & Sinkula (2009), Hussain et al (2019), and Kara et al (2005), Julian (2010) and Wahyono (2017) in their respective studies explain that market orientation has a significant effect on marketing performance. This is also supported by a research conducted by Utaminingsih (2016) which explains that market orientation has a positive and significant effect on marketing performance.…”
Section: Introductionmentioning
confidence: 99%
“…Innovative organizations adapt to the changes in a competitive environment, create new demands in the markets, and continuously try to trigger overall sales by introducing new products and services (Hult et al 2001). Strategic orientations are known as excellent predictors of organizational performance (Beliaeva et al 2020;Hussain and Khan 2019;Kumar et al 2018;Kocak et al 2017); also, strategic orientations predict the organizational tendencies on innovativeness from a broader perspective (Tho 2019;Hult et al 2004). With this study, we examine the technological predictors of technological innovativeness through strategic orientation literature.…”
Section: Strategic Orientationsmentioning
confidence: 99%
“…additionally, competitor-oriented firms are also likely to adopt and implement e-business initiatives. (Hussain and Khan, 2019).…”
Section: -2-1 Customer Orientationmentioning
confidence: 99%
“…The response to these external voices may have an impact on an organization's decision to implement e-marketing methods in some cases. Firms risk losing relationships with their suppliers and customers, as well as social legitimacy in their competitive environment, if they do not invest in e-marketing skills (Hussain and Khan, 2019). Firms are more likely to adjust to their competitive environment and gain an edge by acquiring resources before competitors in extremely unstable environments.…”
Section: -2-2 Competitor Orientationmentioning
confidence: 99%